METODOLOGI TRADISI AJARAN KEJAWEN PANCA EKA LUMAKSANA: MODEL PENENTUAN HARGA JUAL HARMONI - Whedy Prasetyo (Jurnal Akuntansi Aktual, 2017)
This study builds Kejawen tradition teaching of Panca Eka Lumaksana to determine harmony sale pricing. This study is a qualitative research that defines the value of being honorable based on Kejawen Panca Eka Lumaksana norm. This point of view represents Tatanan Paugeraning Urip, Kejawen tradition based on Java cultural life. The data of this study is obtained through participant observation. The results show that concept of sale pricing is not only based on measurable economic value (material) but also based on immeasurable economic values (immaterial). Non-economic value is the result of behavior based on noble characters as a result of the research findings. The concept of harmony sale pricing model is based on theseller intention.Keywords:Kejawen tradition of Panca Eka Lumaksana, economic and immeasurable value, harmony sale pricing, Tatanan Paugeraning Urip